The disparities between B 40 and M 40 on the restraints in order possessing a house in the state of Selangor - Mohamed Osman, Mariana; Zainudin, Farah Eleena; Rabe, Noor Suzilawati (2017)
A shelter is necessary that are crucial as referring to Maslow’s hierarchy of needs. However, owning a home is arduous for low-income earners, especially people who living in a city. People living in a city mostly prefer to rent rather than buying a house due to home prices are too expensive. Access to appropriate, affordable, housing is a fundamental human right, which is essential for individual, family and community wellbeing (ACOSS 2008 in Select Committee 2008, p29). Thus, the perception of the community towards buying a house is very important. Several research questions have been identified through this study. Firstly, what is the main reason among the group of B40 and M40 living in Selangor who were still have a problem on buying a property? Secondly, what is the range of the price of the house that can be afford to buy by the group of B40 and M40 in Selangor? From the research questions, objectives were formulated which are; to identify the reasons of not buying a house and to determine the house price that can afford to buy by the buyers group of B40 and M40. In order to achieve the objectives of the study, the questionnaire survey was conducted in Selangor to obtain the information regarding the affordable housing.